Dificuldades na escrita de alunos do 6º ano do ensino fundamental: uma proposta de trabalho com a ortografia - Roza, Maria Bernadete da (2016)
Portuguese subject has as a purpose of teaching-learning the oral and written language teaching inside of the interaction processes. In this context, the language includes social, historical, cultural and also ideological aspects. In order to contribute to the discipline, the focus of this research are reflections and analysis involving the context of regularities and arbitrariness of the written code, orthography. By studies and classroom observation we inquire: How can we teach orthography for students of the 6th grade of elementary school, who can read and write, but still conceive writing as transposition of speech, unknowing the conventions of regularities and arbitrariness that constitute the language in written form? In order to find answers to this questioning, we aim to check which are the most frequent spelling inadequacies in the spontaneous text productions of the students of 6th grade of elementary school and apply a pedagogical proposal with activities focused on orthographic, providing the student get to writing code domain. Activities guided by reflection on the use of spoken language over the written language, so students can reflect about language in use, and about the relation between speech and writing, regularities and arbitrariness. Taking as theoretical basis Oliveira studies (2005), for the categorization of misspellings, we reflect and analyze these errors based on author as: Kato (1987), Lemle (1990), Cagliari (1992; 1998; 1999; 2002), Bortoni-Ricardo (2004; 2005; 2006), Mitchell (2009, 2012), Mollica (2011), Kings and Tenani (2011), Faraco (2012), Busse (2013; 2015) e Nobrega (2013). It is, therefore, a guided research in Applied Linguistics ethnographic nature (qualitative interpretative), following the research-action model, which aimed to analyze the orthographic writing of the students of 6th grade of elementary school. The data collection was possible through textual diagnostic production, Oliveira (2005) characterization, and application of didactic sequence: gender “causo” focused on orthography. As a result of this research process, we understand that only the reading is not enough to the orthography learning and it needs to be systematized and taught on schools so that the students understand that speech and writing are different in their everyday practices, as well understand the regularities and arbitrariness that involve writing code, always searching in the dictionary, always searching the dictionary whenever a doubt appear in writing.